Atherosclerosis disease management - Suri,Jasjit S.; Kathuria, Chirinjeev; Molinari, Filippo (Springer eBooks., 2011)
Atherosclerosis is a degenerative process affecting blood vessels, which determines narrowing of the lumen, plaque growth, and hardening of the walls. It is a risk factor for cardiovascular diseases. The focus of this book is on the management of the atherosclerotic disease. The coverage spans from histological presentation of the various stages of atherosclerotic lesions to the earliest studies in atherosclerosis therapy, from advanced clinical diagnosis to monitoring, follow-up, and home-care of the atherosclerotic patient. This book shows well-established diagnostic techniques covering several medical imaging modalities such as Ultrasounds, IVUS, MRI, Computer Tomography, along with new trends in early and advanced atherosclerosis diagnosis (innovative drugs and tissue characterization procedures). Surgical standards will be presented along with innovative experimental trials for the treatment of the atherosclerotic patient. The book also covers emerging techniques based on molecular imaging and vibro-acoustics.